The Use of Podcast to Improve Students’ Speaking Achievement at Madrasah Aliyah Aulia Cendekia Palembang - Rizky Eka Fadillah; Jaya Nur Iman; Desi Surayatika (Jurnal Paradigma, 2025)
By integrating podcasts into language instruction, educators can create a more engaging, authentic, and accessible environment for practicing speaking skills. The potential of podcasts to improve speaking proficiency lies in their ability to provide consistent auditory input, expand vocabulary, and model accurate pronunciation. This research, therefore, seeks to explore the impact of podcast use on students' speaking achievement at Madrasah Aulia Cendekia. The study aims to provide insights into how podcasts might bridge the gap between theoretical knowledge and practical application, ultimately fostering a learning experience that better equips students for real-life communicationThis study investigated the effectiveness of using podcast media to improve students'speaking achievement at Madrasah Aliyah Aulia Cendekia Palembang. The study utilized apre-experimental design with a one-group pretest-posttest approach involving 35 students from grade X as participants. For 10 sessions, the students were exposed to podcast-based learning, where they listened to and practiced speaking through various podcast episodes designed to improve their self-introductions, daily routines, hobbies, and personal experiences in English. Data was collected through pre-test and post-test assessments to measure the improvement of students' speaking ability. The results showed a significant improvement in students' speaking achievement, with post- test scores significantly higher than pre-test scores. The findings suggest that podcasts can be an effective tool in improving students' speaking ability by providing engaging and authentic language practice opportunities. The study recommends integrating podcasts into the English curriculum to encourage better speaking ability among students. Keywords: English language learning, podcast, pre- experimental design, speaking achievement ABSTRAK Dengan mengintegrasikan podcast ke dalam pembelajaran bahasa, pendidik dapat menciptakan lingkungan yang lebih menarik, autentik, dan mudah diakses untuk melatih keterampilan berbicara. Potensi podcast dalam meningkatkan kemahiran berbicara terletak pada kemampuannya untuk memberikan input auditori yang konsisten, memperluas kosakata, dan menjadi model pelafalan yang akurat. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi dampak penggunaan podcast terhadap pencapaian berbicara siswa di Madrasah Aliyah Aulia Cendekia. Studi ini bertujuan untuk memberikan wawasan tentang bagaimana podcast dapat menjembatani kesenjangan antara pengetahuan teoretis dan penerapan praktis, sehingga menciptakan pengalaman belajar yang lebih membekali siswa dalam komunikasi kehidupan nyata. Penelitian ini menyelidiki efektivitas penggunaan media podcast untuk meningkatkan pencapaian berbicara siswa di Madrasah Aliyah Aulia Cendekia Palembang. Penelitian ini menggunakan desain pra-eksperimen dengan pendekatan satu kelompok pretest-posttest yang melibatkan 35 siswa kelas X sebagai partisipan. Selama 10 sesi, siswa diberikan pembelajaran berbasis podcast, di mana mereka mendengarkan dan melatih berbicara melalui berbagai episode podcast yang dirancang untuk meningkatkan kemampuan memperkenalkan diri, rutinitas harian, hobi, dan pengalaman pribadi dalam bahasa Inggris. Data dikumpulkan melalui tes awal (pre-test) dan tes akhir (post-test) untuk mengukur peningkatan kemampuan berbicara siswa. Hasil penelitian menunjukkan adanya peningkatan yang signifikan dalam pencapaian berbicara siswa, dengan skor post-test yang jauh lebih tinggi dibandingkan skor pre-test. Temuan ini menunjukkan bahwa podcast dapat menjadi alat yang efektif dalam meningkatkan kemampuan berbicara siswa dengan menyediakan kesempatan latihan bahasa yang menarik dan autentik. Penelitian ini merekomendasikan integrasi podcast ke dalam kurikulum bahasa Inggris untuk mendorong peningkatan kemampuan berbicara siswa. Kata kunci: desain pra-eksperime, podcast, pencapaian berbicara, pembelajaran bahasa Inggris.